Determination and verification of reference interval limits in clinical chemistry$arecommendations for laboratories on behalf of the Working Group Guide Limits of the DGKL with respect to ISO Standard 15189 and the Guideline of the German Medical Association on Quality Assurance in Medical Laboratory Examinations (Rili-BAEK) - Porsch-Özçürümez, Mustafa Kemal; Haeckel, Rainer; Gurr, Eberhard; Streichert, Thomas; Sack, Ulrich (Journal of laboratory medicine, 2019)
Laboratory measurement values require interpretative assistance e.g. so-called guide limits (GL), as an interpretative aid. Legal and normative requirements for medical laboratories do not provide specific information for their implementation and verification. A German Society for Clinical Chemistry and Laboratory Medicine (DGKL) Working Group GL (WG-GL) has, therefore, developed recommendations to support medical laboratories in the management of GL. A specific objective was to create a framework that mainly takes into account those aspects that can be realistically implemented by routine laboratories and that should improve the management of GL of frequently requested quantitative measurement procedures in clinical chemistry. Thus, the focus of these recommendations is on the distinction between reference interval limits and clinical decision limits as well as the determination and verification of reference interval limits. Indirect approaches are highlighted, as they enable routine laboratories with a broad analytical spectrum but limited resources to evaluate or to establish reference limits.
Gesehen am 29.01.2020